Evaluation of 25 midline cerebral structures of infants by three dimensional ultrasound at a public hospital in Malaysia - Norhafidzah, Mohamed Sharif (2017)
Three-dimensional ultrasound (3DUS) examination was available in clinical setting for more than 20 years but 3DUS examination remained underutilized and not widely used in clinical practice. Routinely, in infant brain imaging, following two-dimensional ultrasound (2DUS) examination, Magnetic Resonance Imaging (MRI) examination would be performed for further evaluation of brain pathology if it was indicated. MRI examination had several limitations. 3DUS technique was developed to improve the existing of 2DUS technique. 3DUS had potential to be used broadly in clinical practice. Thus, dependency on MRI examination can be reduced. This study was conducted to determine the potential of 3DUS scanning in evaluating the 25 midline cerebral structures of infant. A total of 20 subjects with mean age of 9.40 ± 5.43 months participated in this study. The subjects underwent 2DUS and 3DUS examination after completed the MRI examination. The images of 25 midline cerebral structures obtained by MRI, 3DUS and 2DUS examination were evaluated by two (2) raters. The data was analyzed using Chi-square test, Cohen’s Kappa test, Intra-class Correlation Coefficient (ICC), Wilcoxon Signed Rank test, Passing-Bablok Regression and Bland Altman Analysis. The raters evaluated most of the midline cerebral structures as excellent in MRI examination as compared to good visualization on 3DUS and non-visualization of image visualization in 2DUS examination respectively. There was no significance difference in disease diagnosis evaluated by raters in MRI examination. The visualization rate was moderate, fair and slight agreement with K < 0.36 at 95% CI and the overall agreement was 20% in 3DUS examination. The ICC was between 0.61 and 0.97 at 95% CI demonstrated good and very good agreement in 3DUS examination. There was no significance difference and no significance bias at 95% CI in measurement of the most of the midline cerebral structures between 3DUS and the both examinations demonstrated that 3DUS was interchangeable and acceptable technique. 3DUS was a reliable technique and can be used as alternative technique for MRI and 2DUS examination. The mean scanning times for 3DUS and 2DUS examination was 5.62 ± 1.92 minutes and 7.07 ± 1.74 minutes respectively, demonstrated that 3DUS was slightly faster than 2DUS examination. 3DUS examination was a reliable, feasible and reproducible technique in measuring the 25 midline cerebral structures. 3DUS examination can be used in clinical setting as alternative examination to MRI and 2DUS examination.